Mechanism of Electron Transfer Reaction of Cr(III) Iminodiacetate Ternary Complex Involving Malonate with N-Bromosuccinimide - Hassan, H.M.; Abdel-Khalek, A.A.; Abo-Elhana, S.H. (JOURNAL OF ADVANCES IN CHEMISTRY, 2011)
The kinetics of oxidation of the chromium (III) complexes, [CrIII(IDA)(Ma)(H2O)]- [IDA=iminodiacetate, Ma=malonic] by N-bromosuccinimide in aqueous solution to yield chromium(IV) has been studied spectrometrically at 25-45°C. The reaction rate increased gradually with increasing pH in the range of (5.75–6.86). The reaction proceeds by one first- order pathway in each reactant. Conformation of the formation of the ternary complex has been done using IR spectrum, TGA, uv-visible spectroscopic and cyclic voltammetry measurements. Thermodynamic activation parameters have been calculated. It is proposed that electron transfer proceeds through an inner- sphere mechanism via coordination of NBS to chromium(III). A common mechanism for this reaction is proposed and supported by an excellent isokinetic relationship between ∆H* and ∆S* values for some ternary chromium(III) complexes.